Practical In situ Calibration for Dose-area Product Meter in Interventional Fluoroscopy: Beam-area Method - Fara Farisa Dhaifina; Raushan Fikr Ilham Ibrahim; Hanendya Disha Randy Raharja; Lukmanda Evan Lubis (Journal of Medical Physics)
The radiation dosimetry used to measure the ionizing radiation dose delivered during X-ray imaging procedures in planar radiography units, especially in fluoroscopy, is the dose-area product (DAP). DAP is used as the primary parameter for recording diagnostic reference levels, which are guidance values for optimizing patient radiation dose. DAP is reported by the system’s DAP meter, which needs to be calibrated appropriately. This study evaluates the influence of dosimeters and field markers on the accuracy of DAP levels in the DAP meter in situ calibration method. The aim of this study is to recommend a combination of dosimeter types and field markers with the highest accuracy for the beam-area method. Two methods of DAP meter in situ calibration were compared: the tandem method with a reference DAP meter as the reference DAP value and the beam-area method using ion chamber dosimeters, solid-state dosimeters, as well as field markers from digital radiography (DR) and computed radiography. This method was applied to the DAP meter in the Allura XPER FD 20 angiography (Philips, Amsterdam, the Netherlands) unit. The results showed that the combination of ion chamber dosimeter and DR field markers at a distance of 55 cm produced the most accurate DAP values (lowest root mean square error value, 0.10). The recommended calibration method can be used to confirm the actual DAP value in X-ray imaging in a planar radiography unit.